Golda Meir and Bruno Kreisky – a political and personal duel - Bachleitner, K (Indiana University Press, 2018)
This article describes the political and personal duel between Golda Meir and Bruno Kreisky. In 1973, the two Socialist statesmen of Jewish origin clashed over the issue of Palestinian terrorism directed against Jewish transit via Vienna, triggering an almost decade-long bilateral crisis between Israel and Austria. For the purpose of better understanding the roots of their animosities, this paper traces and compares the biographies and mind-sets of the two heads of state, arguing that it was the Inner-Jewish divide between Zionist and Diaspora Jews that led to bitter personal and political conflict between Golda Meir and Bruno Kreisky.